Biosynthesis of the Polycyclic System in the Antifungal HSAF and Analogues from Lysobacter enzymogenes. Issue 21 (25th April 2018) - Li, Yaoyao; Wang, Haoxin; Liu, Yan; Jiao, Yujie; Li, Shanren; Shen, Yuemao; Du, Liangcheng
Abstract: The biocontrol agent Lysobacter enzymogenes produces polycyclic tetramate macrolactams (PoTeMs), including the antifungal HSAF. To elucidate the biosynthesis of the cyclic systems, we identified eleven HSAF precursors/analogues with zero, one, two, or three rings through heterologous expression of the HSAF gene cluster. A series of combinatorial gene expression and deletion experiments showed that OX3 is the "gatekeeper" responsible for the formation of the first 5‐membered ring from lysobacterene A, OX1 and OX2 are responsible for formation of the second ring but with different selectivity, and OX4 is responsible for formation of the 6‐membered ring. In vitro experiments showed that OX4 is an NADPH‐dependent enzyme that catalyzes the reductive cyclization of 3‐dehydroxy alteramide C to form 3‐dehydroxy HSAF. Thus, the multiplicity of OX genes is the basis for the structural diversity of the HSAF family, which is the only characterized PoTeM cluster that involves four redox enzymes in the formation of the cyclic system. Abstract : Strong as an OX : Four genes ( OX1–OX4 ) that encode NADPH‐dependent redox enzymes dictate the structural diversity of the antifungal HSAF family of polycyclic tetramate macrolactams from the Gram‐negative gliding bacterium Lysobacter enzymogenes, a potent biocontrol agent and prolific producer of bioactive products.